2018
DOI: 10.5194/bg-2018-459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic (Svalbard Islands) Active and Exported Diatom Stocks and Cell Health Status

Abstract: <p><strong>Abstract.</strong> Diatoms tend to dominate the Arctic spring bloom, a key event in the ecosystem. Large sinking of diatoms is expected at the end of the bloom driven by deteriorated cell status associated to nutrients (silicon) depletion. However, there are few reports on the status of diatoms' health during Arctic blooms and its possible role on sedimentary fluxes. Here we quantify, using the Bottle-Net, Arctic diatom stocks below and above the photic laye… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…(Figure 5). Diatoms are often associated with high export events in the Arctic Ocean as their ability to aggregate increases their sinking speed, especially under nutrient‐limited conditions (Agustí et al., 2020; Roca‐Martí et al., 2017; Smetacek, 1985). Previous studies in the Arctic seasonal ice zone where ice melt induces stratified conditions reported the build‐up of large algal biomasses and high vertical POC and chl a fluxes (Andreassen & Wassmann, 1998; Dybwad et al., 2021; Wassmann & Reigstad, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 5). Diatoms are often associated with high export events in the Arctic Ocean as their ability to aggregate increases their sinking speed, especially under nutrient‐limited conditions (Agustí et al., 2020; Roca‐Martí et al., 2017; Smetacek, 1985). Previous studies in the Arctic seasonal ice zone where ice melt induces stratified conditions reported the build‐up of large algal biomasses and high vertical POC and chl a fluxes (Andreassen & Wassmann, 1998; Dybwad et al., 2021; Wassmann & Reigstad, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Algal bloom build‐up and composition has direct consequences on the export of organic carbon to depth. Single‐celled and chain‐forming diatoms sink rapidly due to their silicified cell walls and are often associated with high export fluxes of carbon (Boyd & Newton, 1999; Dybwad et al., 2021), especially on termination of their growth phase (Agustí et al., 2020; Smetacek, 1985). By contrast, the small flagellate Phaeocystis pouchetii sinks slowly and contributes to lower carbon export efficiency (Reigstad & Wassmann, 2007; Wolf et al., 2016).…”
Section: Introductionmentioning
confidence: 99%